Pengaruh Digital Payment dan E-Commerce terhadap Perilaku Konsumtif: Studi Kasus pada Mahasiswa Fakultas Agama Islam UMSU - Anggi Listia; Mutiah Khaira Sihotang (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Pengaruh Digital Payment dan E-Commerce terhadap Perilaku Konsumtif: Studi Kasus pada Mahasiswa Fakultas Agama Islam UMSU This research aims to find out the influence of digital payments and e-commerce on consumer behavior (case study of students at the Umsu Islamic Faculty) both partially and simultaneously. This research approach is associative. The population was 1,215 students and the sample was 92 students. The data collection technique in this research uses a questionnaire technique. The data analysis technique in this research uses Multiple Linear Regression Analysis Test, Hypothesis Test (t Test and F Test), and Coefficient of Determination. Data processing in this research used the SPSS (Statistical Package for the Social Sciences) software program version 29.00. Partially, the digital payment variable has a significant effect on consumer behavior. Partially, the e-commerce variable has a significant effect on consumer behavior. Simultaneously, digital payment and e-commerce variables have a significant effect on consumer behavior.